A dataset from the Cryptogamia-Lichenes section of the Herbarium Universitatis Taurinensis (TO) - Rosanna Piervittori; Deborah Isocrono; Enrica Matteucci; Mariagrazia Morando; Luca Dessì; Laura Guglielmone; Heimo Rainer; Stefano Martellos; Andrea Moro; Pier Luigi Nimis; Matteo Conti; Sergio Enrico Favero-Longo (Biodiversity Data Journal)
The section Cryptogamia-Lichenes of the Herbarium Universitatis Taurinensis (TO) includes ca. 34,600 lichen specimens, organised in the historical (ca. 30,700 specimens, mostly from the 19th century) and modern (ca. 3,900 specimens collected from 1978, out of which ca. 3400 from Italy) collections. Specimens from the administrative regions of Piemonte and Valle d’Aosta (NW Italy) are the core of the modern collection, documenting floristic and vegetation studies, as well as biomonitoring campaigns and investigations on the biodeterioration of the stone cultural heritage.The dataset of the Italian materials of the modern lichenological collection of TO, with 3,365 samples, is fully georeferenced and accessible in the Global Biodiversity Information Facility (GBIF), in the Jointly Administered Herbarium Management System and Specimen Database (JACQ) and in the Information System of Italian Lichens (ITALIC). With regard to the historical collection, only a set of 59 recently revised specimens is available on the mentioned platforms, but most of the materials are accessible as digital images on the website of the project HERB-TO-CHANGE.